2016
DOI: 10.3389/fmicb.2016.00704
|View full text |Cite
|
Sign up to set email alerts
|

Evasion and Immuno-Endocrine Regulation in Parasite Infection: Two Sides of the Same Coin in Chagas Disease?

Abstract: Chagas disease is a serious illness caused by the protozoan parasite Trypanosoma cruzi. Nearly 30% of chronically infected people develop cardiac, digestive, or mixed alterations, suggesting a broad range of host-parasite interactions that finally impact upon chronic disease outcome. The ability of T. cruzi to persist and cause pathology seems to depend on diverse factors like T. cruzi strains, the infective load and the route of infection, presence of virulence factors, the parasite capacity to avoid protecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 130 publications
0
16
0
Order By: Relevance
“…At this stage, the parasite tends to establish a trade‐off with the host mainly by using a complex network of antioxidant enzymes to shield itself from lysosomal oxygen and nitrogen reactive species (see Ref. ).…”
Section: Protective Immune Response To Acute Trypanosoma Cruzi Infectmentioning
confidence: 99%
See 2 more Smart Citations
“…At this stage, the parasite tends to establish a trade‐off with the host mainly by using a complex network of antioxidant enzymes to shield itself from lysosomal oxygen and nitrogen reactive species (see Ref. ).…”
Section: Protective Immune Response To Acute Trypanosoma Cruzi Infectmentioning
confidence: 99%
“…The effect of increased glucocorticoid levels during the acute phase of the disease ultimately favors parasitism and the establishment of a persistent infection (see Ref. ). The blockade of glucocorticoid receptors did not significantly affect parasitemia and the number of inflammatory foci in the heart, and only a tendency toward decrease in the number of amastigote nests was observed in both strains of mice.…”
Section: The Activity Of the Hpa Axis During Acute T Cruzi Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different studies have demonstrated the crucial role of complement as a first line of defence against T. cruzi infection, as well as in the maintenance of chronic infection and severity of CCC . The complement system includes more than 35 plasma proteins/regulators and cell surface receptors which act together in the recognition and elimination of microbial and foreign cells.…”
Section: Introductionmentioning
confidence: 99%
“…in the maintenance of chronic infection 11 and severity of CCC. [12][13][14][15] The complement system includes more than 35 plasma proteins/regulators and cell surface receptors which act together in the recognition and elimination of microbial and foreign cells.…”
mentioning
confidence: 99%